Nexus between Out of School Children and Child Disability: An Empirical Study based on household survey of Sindh, Pakistan - Jafri, Muhammad Kazim; Khalid, Muhammad; Younus, Muhammad Kamran (Annals of Human and Social Sciences, 2024)
In the contemporary world, no dimension of the world lives long without the aid of Goal-4 of SDGs focuses on inclusive, quality and equity based educational opportunities for everyone. The biggest barrier to achieve this goal is Out of school children. This paper analyses causal factors of this issue from child functioning perspective. This analysis uses microdata of Sindh MICS 2018-19 and the child disability is computed from the Child Functioning Module of the 5-17 Years-Questionnaire. Results of the study reveals that child disability is a significant determinant of out of school children. Female children are mostly likely to be out from the school as compare the male children; poverty also plays the pivotal role to keep children away from school. Children whose mothers are more educated and are living in the richer quintiles, have low risk of being out of school. Difficulties in child functioning domains such as seeing, self-care, communication and making friend are found significant determinants of out of school children.